CHIME ages for granulites from the Napier Complex, East Antarctica - Asami, Masao; Suzuki, Kazuhiro; Grew, Edward S.; Adachi, Mamoru (National Institute of Polar Research, 1998)
P(論文) Th-U-bearmg minerals (monazite, zircon, xenotime and polycrase) in five granulite samples from Mt Riiser-Larsen (MA88022102), Beaver Island (2023B), Reference Peak (2306E and 2306J) and Mt Cronus (2275) in the western Napier Complex of East Antarctica were dated by CHIME on the basis of electron microprobe ThO_2, UO_2 and PbO analyses Rocks from these localities, including some of the studied samples, are characterized by sapphirine-quartz-, orthopyroxene-sillimanite- and osurmlite-beanng mineral assemblages, indicating ultra-high-temperature granuhte-facies metamorphism A few grains of monazite in Sample MA88022102 and of zircon in Sample 2275 are chronologically heterogeneous, but other analyzed grains of monazite and zircon in these samples and all analyzed grains in the other samples, including xenotime, are almost homogeneous The core of a Mt Cronus zircon grain gives the oldest CHIME age, 3646±136 Ma, which could be a minimum age for protolith formation The homogeneous minerals, together with the older domains of Mt Riiser-Larsen zoned monazite and some grains of Mt Cronus zircon, give well-defined isochrons yielding consistent ages of 2404 Ma to 2441 Ma (within±54 Ma) on the ThO_2-PbO or UO_2-PbO plots Data points from zircon in Sample 2306J and from polycrase in Sample 2275 yield no isochron Given the petrographic characteristics of the samples and the high Pb-retentivity of the Th-U-bearmg minerals, we interpret the 2404-2441 Ma CHIME ages to date the ultra-high-temperature granulite-facies metamorphism The 2404-2441 Ma ages lie in the 2400-2500 Ma range of ages reported from numerous localities in the Napier Complex In the absence of decisive evidence for inherited older grains and of significant retrograde features in the analyzed samples, we consider that the Napier ultra-high-temperature metamorphism occurred not -2800 Ma ago as interpreted by most investigators, but 2400-2500 Ma ago departmental bulletin paper